Study of adhesion of "MERON" and "TOTAL-CEM" cements to dentine, cyscium chlorine and dioxide alloy - L. D. Chulak; V. G. Zadorozhny; Yu. L. Chulak; O. L. Chulak; S. S. Nebogatov (Kazimierz Wielki University, 2017)
Analysis of literature data shows that glassless cements of Méron and Total-cem are now widely used in dentistry to fix dental tabs [1]. Therefore, the study of the adhesion of these cements to the dentin and to the inserts of the KHS and zirconium dioxide is very relevant. The authors investigated samples that were obtained by removing single-channel teeth. Then the root canals were subjected to endodontic machining with the subsequent calibration of the rows of the corresponding pin diameter. The results of the conducted studies allow us to conclude that for fixing the inserts from the KSS alloy, it is more expedient to use MERON cement, and for carbide total-Cem carbide inserts from zirconium dioxide.